A Framework for Selecting and Optimizing Color Scheme in Web Design - Ferris, Kevin; Sonya Zhang (2016 49th Hawaii International Conference on System Sciences (HICSS), 2016)
Based on the foundation of color theory, the symbolism and human emotions commonly attached to color, and how these factors can directly influence business branding, we developed a framework that helps web designers to select and optimize color scheme for websites and web applications, while avoiding common pitfalls that drive customers away, and standing out in today's fiercely competitive Internet marketplace. To evaluate the effectiveness of the framework, we conducted an experiment where subjects were asked to design the color scheme for a website. The experimental group was introduced to the web color framework before being evaluated, while the control group was evaluated based only off their personal knowledge and experience. We concluded with overall positive results in favor of the framework.